Motion Sensing Behaviour in Weakly Electric Fish - Young, Colleen (Université d'Ottawa / University of Ottawa, 2014)
Weakly electric fish use of a self-generated electric field to probe their environment, this behaviour is known as electrolocation. This study investigated two aspects of electrolocation in two species of knifefish (Apteronotus leptorhynchus and Eigenmannia virescens). First, we characterized the ability to track moving objects and found that tracking performance did not differ among speeds tested in either species. Second, we characterized a motion-related cue for distance perception, similar to visual parallax, for which rapidly moving objects would be perceived as closer than slowly moving objects. During tracking experiments, the fish remained centered between the moving objects. We hypothesized that the fish use electrosensory parallax to perform this centering behaviour. Thus, we predicted that if one object moved slightly slower than the other, the fish would perceive the slower-moving object as farther away, and would move towards the slower object to remain “centered.” Indeed, our results supported our hypothesis with E. virescens moving towards the slower object to an extent that increased with the relative decrease in speed.
Keywords: weakly electric fish; electrolocation; tracking; motion parallax